Atomic‐Resolution Three‐Dimensional Structure of Amyloid β Fibrils Bearing the Osaka Mutation. Issue 1 (13th November 2014) - Schütz, Anne K.; Vagt, Toni; Huber, Matthias; Ovchinnikova, Oxana Y.; Cadalbert, Riccardo; Wall, Joseph; Güntert, Peter; Böckmann, Anja; Glockshuber, Rudi; Meier, Beat H.
Abstract: Despite its central importance for understanding the molecular basis of Alzheimer's disease (AD), high‐resolution structural information on amyloid β‐peptide (Aβ) fibrils, which are intimately linked with AD, is scarce. We report an atomic‐resolution fibril structure of the Aβ1‐40 peptide with the Osaka mutation (E22Δ), associated with early‐onset AD. The structure, which differs substantially from all previously proposed models, is based on a large number of unambiguous intra‐ and intermolecular solid‐state NMR distance restraints. Abstract : A fold not observed before : The atomic‐resolution fibril structure of the Aβ1‐40 peptide with the Osaka mutation (E22Δ), which is associated with early‐onset Alzheimer's disease, differs substantially from all previously proposed models. In this complex structure the deletion mutation is found in a β turn.